2016
DOI: 10.1212/wnl.0000000000003029
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genetic factors in pediatric inflammatory demyelinating diseases

Abstract: The onset of multiple sclerosis (MS) occurs in childhood in about 5% of all patients with MS. The disease in adults has a complex genetic and environmental inheritability. One of the main risk factors, also confirmed in pediatric MS, is HLA DRB1*1501. In addition to genetic factors, a large part of disease susceptibility in adults is conferred by environmental risk factors such as low vitamin D status, exposure to cigarette smoking, and remote Epstein-Barr virus (EBV) infection. In children, both exposure to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…The association between neonatal levels of vitamin D and future risk of multiple sclerosis is controversial. 42 A Swedish population-based case-control study with 459 individuals with multiple sclerosis showed no association; however, the results may have been affected by degradation of 25-hydroxyvitamin D owing to high storage temperatures of dried blood spot samples. 43 Contrastingly, a similarly designed Danish case-control study that measured 25-hydroxyvitamin D levels on dried blood spot samples showed an association between low concentrations of neonatal vitamin D and increased risk of multiple sclerosis.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 96%
See 1 more Smart Citation
“…The association between neonatal levels of vitamin D and future risk of multiple sclerosis is controversial. 42 A Swedish population-based case-control study with 459 individuals with multiple sclerosis showed no association; however, the results may have been affected by degradation of 25-hydroxyvitamin D owing to high storage temperatures of dried blood spot samples. 43 Contrastingly, a similarly designed Danish case-control study that measured 25-hydroxyvitamin D levels on dried blood spot samples showed an association between low concentrations of neonatal vitamin D and increased risk of multiple sclerosis.…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 96%
“…Low vitamin D status has been consistently associated with disease susceptibility in adult‐onset multiple sclerosis. The association between neonatal levels of vitamin D and future risk of multiple sclerosis is controversial . A Swedish population‐based case–control study with 459 individuals with multiple sclerosis showed no association; however, the results may have been affected by degradation of 25‐hydroxyvitamin D owing to high storage temperatures of dried blood spot samples .…”
Section: Environmental and Genetic Risk Factors: The Complex Interplaymentioning
confidence: 99%
“…With respect to adult MS, the pediatric form offers the unique possibility to better explore environmental factors associated to the risk of developing MS and relapses, as confounding factors occurring along the course of MS are less present [104]. Studies in children and adolescents have pointed out that an increased risk of MS is related to previous exposure to passive smoking [105], to Epstein-Barr virus (demonstrated by two independent studies [106,107]), and to BMI [108].…”
Section: Mri: a True Distinctive Pattern In Ped-ms?mentioning
confidence: 99%
“…Perhaps it is because the process of brain development is more complete; myelination is now well established and "compacted" throughout the brain. This gives HHV-6, should it get "riled up" by any agent or event, an opportunity to create "plaques", the hallmark of MS [33], through withdrawal of lamellae by groups of neighboring, infected oligodendrocytes, leaving whitishlooking patches of demyelinated brain tissue here and there when the brain is examined by MRI or at autopsy. Plaques appear to be lacking in brains of autistic younger children.…”
Section: Ages 6 -12+ Years: Childhood Msmentioning
confidence: 99%
“…Then came more specific, antibody-mediated stains such as glial fibrillary protein (GFAP) for astrocytes and myelin oligodendrocyte protein (MOG) for oligodendrocytes. The hallmark of MS is the classic plaque [33,[35][36][37], one of numerous, often extensive whitish regions in autopsy MS brain sections that stain strongly for GFAP, a marker for astrocytes, and poorly for myelin proteins, suggesting that this is a demyelinated area full of dead astrocytes, the so-called "glial scar". MS plaques also often contain evidence of inflammatory processes, such as of perivascular arrays of lymphocytes, and macrophages/microglia that stain for phagocytized myelin proteins.…”
Section: The Staining Problem In Glial Cells In Ms and Pml -Gliogenesmentioning
confidence: 99%